Democracy and the All-Affected Principle - Lagerspetz, Eerik (Res Cogitans, 2015)
The All-Affected Principle has an important status in recent theoretical discussions on democracy. According to the principle, all who are affected by a decision should have a right to participate into making it. The principle is supposed to ground the right or optimal boundaries of democratic decision-making units. This paper is basically a critique of the principle. In the first parts of the paper, the All-Affected Principle is distinguished from some related principles. However, even a more precise version of the principle is still troubled by ambiguities. It is argued that Robert Goodin’s expansive reading is the only coherent one. However, if it is accepted, the principle cannot be used for its original purpose. The last parts focus on some largely unexamined aspects of the principle. First, the principle also works as a means of exclusion, not only of inclusion. Second, if, as the principle says, participation rights are based on interests, it is by no means obvious that these rights should be equal. Third, the principle cannot provide us with a non-institutional starting point. Nevertheless, a much weaker form of the principle may be plausible.